Expandable silica particles
By coating kaolin and talc powder on the outer surface of expandable silica particles, the risk of adhesion and melting at high temperatures is solved, and the strength and water absorption resistance of the particles are improved, and their excellent properties in matrix materials are maintained.
Patent Information
- Application Number
- CN202180034048.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-04
- Filing Date
- 2021-05-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-05-10
AI Technical Summary
At temperatures close to the plastic-melting state transition, the expanded silica particles are prone to adhere to each other and/or to the furnace, and the risk of internal pore wall rupture and outer surface pore collapse increases, resulting in weakening of physical properties of the expanded silica particles and increasing water absorption.
Expandable silica particles containing silica powder, fume and expansion agent are used and coated with kaolin and talc powder on their outer surfaces to reduce the risk of adhesion and melting and enhance the elasticity of the particles and the sealing of the pores.
It effectively reduces the risk of expandable silica particles adhesion and melting at high temperatures, reduces the possibility of pore wall rupture and pore collapse, thereby improving the strength and water absorption resistance of the particles, and maintaining their excellent properties in matrix materials.
Smart Images

Figure CN115515896B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to expandable silica particles, a method for expanding silica particles, expanded silica particles produced by the method, uses of the expanded silica particles and a method for producing expandable silica particles. Background Art
[0002] Expanded silica particles are used in various fields, for example as fillers in matrix materials such as concrete or epoxy resins, as insulating materials together with various adhesive materials, or as water filtration media. Several favorable physical properties are associated with expanded silica particles, such as low density, high dimensional stability, excellent compressive strength and high insulating capacity. Expanded silica particles added to matrix materials can also improve the processability of matrix materials before hardening, for example by improving fluidity under very low water absorption. In addition, expanded silica particles can reduce overall material costs, particularly for expensive matrix materials. Finally, expanded silica materials contribute to environmental sustainability by using recycled glass after consumption.
[0003] During the production of expanded silica particles, it is desirable to use the expanded silica particles close to the temperature at which the expanded silica particles are converted from a plastic state to a molten state. At these temperatures, the material of the expanded silica particles provides the minimum resistance to the ongoing expansion. Thus, a more optimal expansion and a more uniform spherical shape of the expanded silica particles are achieved. However, since the expanded silica particles are close to the conversion from a plastic state to a molten state, problems may arise in the commonly used methods. Close to this conversion, the expanded silica particles are more likely to adhere to each other and to the surrounding furnace in which the particles expand. Although kaolin coatings can be used as release agents, kaolin is converted into metakaolin near the plastic-melting transition temperature, and most of its properties as a release agent can be lost thereby. Metakaolin can also be melted into the surface of the softened expanded silica particles, thereby further reducing its effect as a release agent.
[0004] In addition, due to the low viscosity at temperatures close to the transition from the plastic state to the molten state, the internal cell walls can break, resulting in an open-cell internal structure, and the pores at the outer surface of the expanded silica particles can collapse. When using kaolin coatings as release agents, the surface of the expanded silica particles can become more brittle, resulting in further risks of pore collapse at the outer surface and thus cracking of physical properties. These effects can lead to weakened expanded silica particles and the ability of expanded silica particles to absorb fluids such as water. Especially when used as a filler in a matrix material, such as an organic or inorganic adhesive, the high absorption capacity can cause the expanded silica particles to absorb a large amount of matrix material. The absorption of such a matrix material negatively affects the properties of the expanded silica particles as a filler material. For example, absorption of concrete additives such as water reducers and gas storage agents will have an important impact on flow behavior and mechanical properties in the cured state. This offsets the desired effect of reducing the overall material density of the matrix and filler.
[0005] Therefore, there is a clear need for improved expandable silica particles that can expand at temperatures close to the plastic-melt transition while reducing the risk of the softened expandable silica particles adhering to each other and / or to the furnace and reducing the risk of internal pore wall rupture and pore collapse at the outer surface. Summary of the invention
[0006] The present disclosure relates to expandable silica particles according to claim 1 and to a method for producing expandable silica particles according to claim 8. The present disclosure also relates to a method for producing expanded silica particles according to claim 10, expanded silica particles according to claim 13 and the use of expanded silica particles according to claim 14. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 A schematic diagram shows a furnace for heating expandable silica particles according to the disclosure. DETAILED DESCRIPTION
[0008] Expandable silica particles according to the present disclosure include silica powder, silica fume and at least one swelling agent. Expandable silica particles also include a coating provided on the outer surface of the expandable silica particles, wherein the coating includes kaolin powder and talcum powder. Advantageously, kaolin acts as a demoulding agent, and talc offsets the negative effects of kaolin at high temperatures by making the outer surface of the expanded silica particles more elastic and having closed pores. Optionally, expandable silica particles may also include other additives such as colorants. Expandable silica particles may have a bulk density of 0.3-1.7kg / l, preferably 0.5-1.5kg / l. Expandable silica particles may have a diameter of 0.1-40mm, preferably 0.25-5.6mm, most preferably 0.8-1.6mm.
[0009] The expandable silica granules comprise 50-98% by weight of silica powder. The particles of the silica powder may have a diameter of 0.01-700 μm. Preferably, the silica powder comprises recycled glass powder. The recycled glass powder may, for example, originate from post-consumer recycled glass, soda-lime glass, float glass, windshields, solar panels. Advantageously, the expandable silica granules thus form an environmentally friendly material.
[0010] The expandable silica particles may contain 0.85-10 wt % of at least one expander. The expander may comprise a powder. Preferably, the particles of the expander powder have a diameter of 0.01-40.0 μm. The at least one expander may comprise aluminum nitride (AlN), silicon carbide (SiC), manganese dioxide (MnO 2 ), sodium carbonate (Na 3 CO 3 ), calcium sodium carbonate (CaNa 3 CO 3 ) or a combination thereof. Preferably, at least one expansion agent comprises silicon carbide powder.
[0011] The expandable silica particles may contain 0.01-10% by weight of silica fume. The silica fume contains ultrafine silica particles having a particle diameter of less than 1 μm. Preferably, the diameter of the silica fume particles is about 150 nm. Advantageously, the silica fume strengthens the pore walls formed in the expandable silica particles during expansion. As a result, the rupture of the pore walls during expansion is reduced. Due to the strengthened pore walls and due to the reduced occurrence of pore wall rupture, the resulting expanded silica particles have a higher strength and a higher resistance to crushing and a significantly reduced water absorption rate.
[0012] The coating may contain 0.5-10 wt.% kaolin powder (Al 2 SiO 5 (HO) 4). Advantageously, kaolin acts as a release agent. As a result, the risk of expandable silica particles adhering to each other and / or to the furnace is reduced. This is particularly important for large production runs of many particles that are expanded simultaneously. However, endothermic dehydration of kaolin occurs in the temperature interval 560-950° C., producing metakaolin, which will gradually reduce the effect of kaolin as a release agent. Therefore, the coating also contains talc powder (Mg 3 Si 4 O 10 (OH) 2 ). The coating may comprise 0.5-5 wt% talc. Advantageously, during expansion, the talc melts into the surface of the expanded silica particles and makes the surface more elastic or flexible, thereby reducing the collapse of pores at the outer surface of the expanded silica particles. Thus, the talc counteracts the adverse effects of kaolin occurring at high temperatures and acts to maintain the surface integrity of the expanded silica particles. Thus, resistance to fluid absorption in the expanded silica particles is improved.
[0013] Next, a method for preparing one or more expandable silica particles according to the present disclosure is described. The method includes providing expandable silica pre-particles (pre-particles) comprising silica powder, silica ash and at least one expansion agent. Providing expandable silica pre-particles may include sintering or hot pressing a mixture of silica powder, silica ash and at least one expansion agent at a temperature less than the activation temperature of at least one expansion agent into a block. Then, the block may be divided into expandable silica pre-particles, for example, by cutting or by crushing the sintered block into pellets. The pellets may be filtered according to size and the large pellets may undergo further separation. Alternatively, a mixture of silica powder, silica ash and at least one expansion agent may be directly hot pressed into expandable silica pre-particles. Alternatively, a mixture of silica powder, silica ash and at least one expansion agent may be provided together with a binder and processed in an industrial granulator. The method of preparing one or more expandable silica particles further comprises the step of coating the outer surface of the expandable silica pre-particles with a coating comprising kaolin and talc, thereby forming expandable silica particles.
[0014] The method for producing expanded silica particles includes providing a plurality of expandable silica particles according to the present disclosure and heating the expandable silica particles in a chamber 2 of a furnace 1 to a temperature greater than the activation temperature of an expander to form expanded silica particles. The expandable silica particles may be added to the chamber 2 ( Figure 1). In chamber 2, expandable silica particles can be fed onto an angled vibrating plate. Direct high-frequency motion can thereby be induced in the expandable silica particles, wherein the motion can be chaotic or turbulent. Preferably, the expandable silica particles can first be fed into a preheating chamber before feeding or conveying into chamber 2. Advantageously, the temperature difference between the core and the surface of the expandable silica particles is minimized during the preheating. In chamber 2, the expandable silica particles are heated to a temperature greater than the activation temperature of the expansion agent, to a temperature of 560-950° C., preferably 850-900° C. During the heating, the expandable silica particles soften. Above the activation temperature of the expansion agent, an exothermic reaction occurs, driving the expansion of the softened particles. Advantageously, the coating on the outer surface of the expandable silica particles insulates the outer surface during the exothermic driven expansion. Thereby, the expansion process is counteracted at the surface of the expanded silica particles, resulting in a denser outer surface of the expanded silica particles, and less open pores, compared to particles without a coating.
[0015] In the chamber 2, the temperature and the residence time can be controlled, thereby controlling the expansion rate of the expandable silica particles. The residence time can be controlled by controlling the conveying speed of the particles in the chamber 2. The furnace 1 may also include a vibrating plate 3, forming the bottom of the chamber 2. The vibrating plate 3 is preferably inclined at an inclination angle relative to the horizontal direction from the inlet downward to the outlet of the furnace. The vibrating plate 3 is vibrated during the heating and expansion of the expandable silica particles, thereby causing movement in the expandable silica particles. Advantageously, the contact time between the silica particles in the furnace 1 is thereby limited, minimizing the risk of the particles adhering to each other and to the furnace.
[0016] On leaving the furnace 1, the expanded silica particles may enter a cooling zone, which comprises one or more stages maintained at a gradually decreasing temperature. In the cooling zone, the expanded silica particles are preferably cooled to ambient temperature, allowing further processing of the expanded silica particles. Within the cooling zone, the temperature and residence time of each stage may be controlled, thereby controlling the cooling rate of the expanded silica particles. Advantageously, the inherent tension within the expanded silica particles due to different cooling rates at the particle surface and in the interior of the particles may thereby be minimized. After cooling, the expanded silica particles may be coated with a sodium silicate solution (also known as water glass), preferably at a temperature of 0.1-200°C. Advantageously, the sodium silicate solution also reduces the surface porosity of the expandable silica particles, thereby improving resistance to fluid absorption in the expanded silica particles.
[0017] The expanded silica particles according to the present disclosure preferably have a bulk density of 150-900 g / l. Preferably, the expanded silica particles have a spherical or nearly spherical shape. The expanded silica particles can be used as fillers in concrete, plaster, gypsum, mortar, epoxy resin, polyurethane, acrylate or suitable organic adhesive, or artificial turf, or as fillers in water filter boxes. Advantageously, the expanded silica particles have a significantly reduced fluid absorption capacity and can, for example, absorb negligible amounts of concrete additives when used as fillers in concrete matrix materials.
[0018] Example 1
[0019] Expandable silica pre-particles are provided by sintering 95 wt% of silica powder, 3 wt% of SiC powder expander and 2 wt% of silica fume into blocks at 710°C. The silica powder contains recycled flat glass. The SiC powder has a particle diameter of 0.01-2 μm. Then, the sintered block is broken into expandable pre-particles, and the expandable pre-particles are filtered according to the particle diameter. The expandable pre-particles are dry-coated with a coating containing kaolin powder and talc powder to form expandable silica particles. The expandable silica particles contain 91.2 wt% of silica powder, 2.88 wt% of SiC powder, 1.92 wt% of silica fume, 2 wt% of kaolin powder and 2 wt% of talc powder. Before being heated to 870°C for 36 s, the expandable silica particles are preheated at 680°C for 300 s. Then, heating was continued at 865°C for 45s and at 860°C for 45s before cooling was started at 200°C for 18s. The resulting expanded silica granules had a bulk density of 275 g / l (determined according to UNI EN 1097-6:2013, Annex C) and a diameter of 2-8 mm (determined according to the sieving method of UNI EN 933-1:2012). The crushing resistance of the expanded silica granules (determined according to UNI EN 13055-1:2003, Annex A, paragraph 4.10) was measured to be 6.19 N / mm 2 The water absorption, determined according to UNI EN 1097-6:2013 (Annex C - Absorption after 5 minutes), was measured to be 4.4%.
[0020] Comparative Example
[0021] Expandable silica pre-particles are provided by sintering 97% by weight of silica powder and 3% by weight of SiC powder expander into blocks at 710°C. The silica powder contains recycled flat glass. The SiC powder has a particle diameter of 0.01-2 μm. Then, the sintered block is broken into expandable pre-particles, and the expandable pre-particles are filtered according to the particle diameter. The expandable pre-particles are then dry-coated with a coating containing kaolin powder to form expandable silica particles. The expandable silica particles contain 93.12% by weight of silica powder, 2.88% by weight of SiC expander and 4% by weight of kaolin coating. The expandable silica particles are heated and cooled in the same manner as in Example 1. The bulk density, particle diameter, water absorption and crushing resistance are measured according to the same standards as described in Example 1. The obtained expanded silica particles had a particle diameter of 2-8 mm, a bulk density of 300 g / l for the particle diameter of 2-4 mm and a bulk density of 275 g / l for the particle diameter of 4-8 mm. The expanded silica particles had a water absorption of 24.2% for the particle diameter of 2-4 mm and 21.9% for the particle diameter of 4-8 mm. Finally, the expanded silica particles in the comparative example had a crushing resistance of 3.5 N / mm for the particle diameter of 2-4 mm. 2 and 2.7 N / mm for particles with a diameter of 4-8 mm 2 .
Claims
1. Expandable silicon dioxide particles, comprising: 50-98% by weight of silicon dioxide powder, 0.85-10% by weight of at least one swelling agent, 0.01-10 wt% silica fume, and A coating is provided on the outer surface of expandable silica particles, wherein the coating comprises kaolin powder and talc powder.
2. Expandable silica granules according to claim 1, wherein the silica powder comprises recycled glass powder.
3. Expandable silica particles according to claim 1 or 2, wherein at least one expander comprises a powder comprising aluminum nitride, silicon carbide, manganese dioxide, sodium carbonate, sodium calcium carbonate or a combination thereof; and wherein the particles of the expander powder preferably have a diameter of 0.01-40 μm.
4. Expandable silica granules according to claim 1 or 2, wherein at least one expanding agent comprises silicon carbide powder.
5. The expandable silica granules according to claim 1 or 2, wherein the expandable silica granules have a diameter of 0.25-5.6 mm.
6. The expandable silica granules according to claim 1 or 2, wherein the expandable silica granules have a bulk density of 0.3-1.7 kg / l.
7. A process for preparing one or more expandable silica particles according to any one of claims 1 to 6, the process comprising: providing an expandable silica precursor particle comprising 50-98 wt % silica powder, 0.01-10 wt % silica fume, and 0.85-10 wt % of at least one expander; and The expandable silica pre-particles are dry coated with a coating comprising kaolin and talc to form expandable silica particles.
8. The method of claim 7, wherein the step of providing expandable silica precursor particles comprises: sintering or hot pressing a mixture of silicon dioxide powder, silicon fume and at least one expanding agent into a block at a temperature less than an activation temperature of the at least one expanding agent; and The mass is divided into expandable silica precursor particles.
Citation Information
Patent Citations
Silica-coated expanding agents and their use in cementitious systems
CN109071350A
Core-shell expanding agents and their use in cementitious systems
CN111132754A